2018
DOI: 10.1016/j.jpowsour.2017.12.042
|View full text |Cite
|
Sign up to set email alerts
|

Competing forces in liquid metal electrodes and batteries

Abstract: Liquid metal batteries are proposed for low-cost grid scale energy storage. During their operation, solid intermetallic phases often form in the cathode and are known to limit the capacity of the cell. Fluid flow in the liquid electrodes can enhance mass transfer and reduce the formation of localized intermetallics, and fluid flow can be promoted by careful choice of the locations and topology of a battery's electrical connections. In this context we study four phenomena that drive flow: Rayleigh-B\'enard conv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 90 publications
4
42
1
Order By: Relevance
“…Specifically, we would like to extend the model by convection [18,19], heat transfer [73,77] and electrode kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we would like to extend the model by convection [18,19], heat transfer [73,77] and electrode kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that fluid motion can be triggered by magnetohydrodynamic effects, i.e., the interaction of a magnetic field (either a background field or the field caused by the battery current) with the cell current. This includes the Tayler instability [11][12][13][14][15][16], electro-vortex flows [17][18][19][20][21] as well as interface instabilities [22][23][24][25][26][27]. While the Tayler instability will get substantial only for large system (in the order of meters) [14], electro-vortex flow will appear already in small cells [19].…”
Section: Introductionmentioning
confidence: 99%
“…5b). The appearance of such azimuthal swirl flow is well known from experiments [43,85,103] and can be easily explained. Radial cell currents and a vertical magnetic background field lead to azimuthal Lorentz forces [87,92,103].…”
Section: Resultsmentioning
confidence: 74%
“…with t, u, p, ν, ρ, µ 0 , r and dV denoting the time, the velocity, the pressure, the kinematic viscosity, the density, the vacuum permeability, the coordinate and the differential volume, respectively. The fluid mesh has at least 200 cells on the diameter, which is fine enough according to [43].…”
Section: Numerical Modelmentioning
confidence: 99%
See 1 more Smart Citation